The identity of Equatobursa, with proposal of new genus and species level synonymies (Hemiptera: Heteroptera: Heterogastridae) - Gao, Cuiqing; Rédei, Dávid (Zootaxa, 2017)
The identities of the genus Equatobursa Zou, 1985 and its single included species, E. nigra Zou, 1985 (Hemiptera: Heteroptera: Lygaeoidea: Heterogastridae) are clarified based on the re-examination of the type material of the species. The following new subjective synonymies are proposed: Sadoletus Distant, 1903 = Equatobursa Zou, 1985, syn. nov.; Sadoletus izzardi Hidaka, 1959 = Equatobursa nigra Zou, 1985, syn. nov.